Penton valves and pipes at Hercules Parlin plant - Hercules Incorporated (1960)
Close-up view of solid Penton needle and plug valves, as well as Penton pipes and fittings, at the Hercules Powder Company plant located in Parlin, New Jersey. Penton was a Hercules-branded chlorinated polyether used as an ingredient in protective coatings for structural steel and other metals, papers, cardboard, and plastics. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Valves; Hercules Incorporated; Corporations; Polyethers; Machinery